The New Framework Planned for the Legal Recognition and Regulation of Muslim Marriages in a Secular South Africa: From Litigation to Law Reform - Najma Moosa; Muneer Abduroaf (AHKAM : Jurnal Ilmu Syariah, 2022)
Muslims, who originate from the East Indies and the Indian sub-continent, have a history in South Africa dating back more than three centuries. Attempts by South African Muslims to have their Muslim marriages (nikāḥs) recognized have a history spanning more than three decades, starting during white minority or apartheid rule and concluding during democracy. Although the Constitution of the Republic of South Africa, 1996, makes provision for Muslim marriages to be formally and separately recognized through legislation, it is a travesty of justice that there is, to date, no legislative framework for the recognition and regulation of the consequences flowing from such marriages. This article critically analyses recent and current litigation and judicial developments and parallel law reform and policy processes pertaining to the formal, future recognition and regulation of Muslim marriages in South Africa. As such, it does not provide any detail regarding why Muslim marriages remain unrecognized or the substantive law content and regulation of Muslim marriages.  AbstrakUmat Islam yang berasal dari Hindia Timur dan anak benua India, memiliki sejarah di Afrika Selatan lebih dari tiga abad. Upaya Muslim Afrika Selatan untuk mengakui pernikahan Muslim mereka memiliki sejarah lebih dari tiga dekade, dimulai pada masa pemerintahan minoritas kulit putih atau apartheid dan berakhir selama demokrasi. Meskipun Konstitusi Republik Afrika Selatan, 1996, membuat ketentuan agar pernikahan Muslim diakui secara formal dan terpisah melalui undang-undang, namun hal itu adalah sebuah ironi keadilan bahwa hingga saat ini, tidak ada kerangka legislatif untuk pengakuan dan pengaturan konsekuensinya. Berdasarkan hal itu, artikel ini secara kritis menganalisis perkembangan litigasi dan peradilan saat ini serta reformasi hukum dan proses kebijakan yang berkaitan dengan pengakuan formal dan masa depan pernikahan Muslim di Afrika Selatan. Kerangka hukum tersebut tidak memberikan rincian apapun mengenai mengapa pernikahan Muslim tetap tidak diakui atau isi hukum substantif dan peraturan pernikahan Muslim.